2015
DOI: 10.12693/aphyspola.128.b-219
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Optical Characterization of CdSe Thin Films Grown by Chemical Bath Deposition

Abstract: Cadmium selenide thin films with different pH values (pH = 10, 11, 12 and 13) are produced on glass substrates at 50• C for 3 h by chemical bath deposition technique. The structural, morphological and optical properties of the films are characterized by X-ray diffraction, scanning electron microscopy and optical absorption spectroscopy, respectively. The obtained films have hexagonal structure. The optical transparency of the films varies between 85% and 98% at wavelength of λ = 550 nm. The scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Scanning electron microscopy studies reveal that the corn-like nanowire with the diameter of 30-50 nm could be observed at higher annealing temperature (300-500 °C), can improve the efficiency of the solar cell. Highly crystallized hexagonal CdSe films were synthesized at pH 10, 180 minutes and 50 °C 66 . Nanorod morphology (length range from 20-85.5 µm, width range from 1.8-10.9 µm) with variable film thickness (465 to 605 nm) was successfully prepared using a chemical bath deposition method.…”
Section: Chemical Bath Deposited Cadmium Selenide Thin Filmsmentioning
confidence: 99%
“…Scanning electron microscopy studies reveal that the corn-like nanowire with the diameter of 30-50 nm could be observed at higher annealing temperature (300-500 °C), can improve the efficiency of the solar cell. Highly crystallized hexagonal CdSe films were synthesized at pH 10, 180 minutes and 50 °C 66 . Nanorod morphology (length range from 20-85.5 µm, width range from 1.8-10.9 µm) with variable film thickness (465 to 605 nm) was successfully prepared using a chemical bath deposition method.…”
Section: Chemical Bath Deposited Cadmium Selenide Thin Filmsmentioning
confidence: 99%
“…Large numbers of binary semiconductors compound like CdS [15][16][17], CdSe [18][19][20], PbS [21][22][23], CuS [24][25][26], and ZnS [27][28][29] can be deposited as thin films using CBD method. For the deposition of ZnS thin films via CBD, some factors should be considered and controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Light with wavelengths of 380-780 nm is called visible light. Visible light consists of purple, blue, green, yellow, orange, and red colors, depending on the wavelength [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%